Prevention of Bullying Behavior through the Roots Program - Nengsi, Ratika; Subaedah (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
The study aims to identify the bullying of students and the preventive efforts of the school through the Roots School Movement program. This type of research is qualitative descriptive with a phenomenological approach, and the research location is in the 7th Makassar State High School. The population in this study is the head of school, teachers, and pupils with sampling techniques using probability random samplings. Data collection techniques are done using observations, interviews, and documentation; then, data will be analyzed using triangulation data, i.e., data collection, data reduction, and verification. Based on the research results, conversation forms often occur in both verbal and non-verbal forms. The verbal conversations experienced by the students are extortion, body shaming, kissing, igniting, and exorcism. Whereas the non-verbal negotiations that occur with the pupils are deliberately pushed and beaten. This beating is done between individuals and individuals, groups to individuals, and groups to groups. So based on that, the things that the 7 Makassar State High Schools are doing in dealing with the negotiations are forming anti-negotiation teams, socializing, forming pupils as anti-counseling agents, training teachers, training pupils, anti-conversion exhibitions for pupils and activating school committees and changing the learning paradigm between teachers and pupils.